Franciscan Tradition in Management and Leadership Thinking Today - Markus Warode (Religions, 2018)
What can we learn from the Franciscan Tradition for the management world today? This research question has lead the research at the Philosophical-Theological College of the German Capuchins for many years. In this paper we focus on the 800-year history of the Franciscan family as a learning organization in order to explore the question of transformation as a key concept of Franciscan life resp. Franciscan leadership. To do so we look at the founder of the Order, Francis of Assisi (1181⁻1226) first. Francis himself stands for a personal, continuous process of transformation in which he chooses the Gospel as a basic orientation for his life. He completely changed his life goals and defines the identity of the entire Franciscan organization. In this context, the core values of the Franciscans, such as evangelical poverty, serving character, and the aspect of brotherhood will be discussed. The Franciscan Community serves as a perfect field of practice for bringing together attitude and action. Finally, practical experiences from the Franciscan tradition, like developing of structural elements (e.g., the annual chapters) are related to the management context. By focusing on the practice and the focus on transformation, the Franciscan example can inspire modern organizations.